Fransa'daki Türk diasporasının kimliğinin korunmasına yönelik faaliyetler - YILMAZ, ALİ (My University, 2021)
There have been labor migration since 1960s to various countries of Europe, particularly to Germany. One of the countries that Turkish workers migrate to through labor migration is France. Although those migrating people plan to come back to Turkey, their homeland, after some time of working, they have become permanent by taking their parents by derivative visa. As aresult of extension of the families and rise of labor migration, the number of Turks in France has increased to 800.000 these days. Coming to stay in France has made the conservation of their identity necessary and the actions have been put into practice just after the labor migration. And in this study in which document analysis of qualitative research has been used, it is aimed to be studied the actions towards conservation of identity of Turkish diaspora in France. In this context, the actions of turkish education, native language of Turks, and religious needs have been studied. As a result of this study, it is understood that Turkish people living in France, are sensitive about conserving their identities and pay attention to those actions. Besides, it is determined that the State of theTurkish Republic carrries out the actions towards conservation of the identity of Turkish people and those actions has increased in historical process. In addition to this, it is understood that in teaching of Turkish language which is the native language of Turks, educational consultancy, related office of educational attaché, and turkish language teachers employed by Turkish Republic have an important place. Finally, it is understood that turkish directorate of religious affairs, religious officials employed in France and DİTİB associations take an active role in meeting the religious needs of Turkish people in France.

Başta Almanya olmak üzere Avrupa’nın çeşitli ülkelerine 1960’lı yıllardan itibaren işçi göçleri yaşanmıştır. Türklerin işçi olarak göç etmiş olduğu Avrupa ülkelerinden biri de Fransa’dır. Fransa’ya giden bu bireyler, bir süre çalıştıktan sonra anavatanları olan Türkiye’ye geri dönmeyi planlasalar da aile birleşimi politikası ile ailelerini yanlarına almalarıyla birlikte Fransa’da kalıcı hale gelmişlerdir. Ailelerin genişlemesi ve işçi göçlerinin artması ile birlikte Fransa’daki Türklerin sayısı her geçen gün artmış ve günümüzde 800.000 civarına ulaşmıştır. Fransa’da kalıcı olmaları Türklerin kimliklerini korumaları gerekliliğini ortaya çıkarmış ve buna yönelik çalışmalar işçi göçlerinin hemen ardından başlatılmıştır. Nitel araştırma yöntemlerinden doküman analizi kullanılarak gerçekleştirilen bu çalışmada da Fransa’daki Türk Diasporasının kimliğinin korunmasına yönelik faaliyetlerin incelenmesi amaçlanmıştır. Bu bağlamda Fransa’da yaşayan Türklerin anadili olan Türkçe’nin eğitimine yönelik faaliyetler ve dini ihtiyaçlarına yönelik faaliyetler incelenmiştir. Araştırma sonucunda; Fransa’da yaşayan Türklerin, kimliklerini koruma konusunda hassas oldukları ve buna yönelik çalışmalara önem verdikleri görülmüştür. Ayrıca Türkiye Cumhuriyeti Devleti’nin, Fransa’daki Türklerin kimliklerinin korunmasına yönelik faaliyetler yürüttüğü ve tarihi süreçte bu faaliyetlerin arttırıldığı belirlenmiştir. Bunun yanı sıra Türklerin anadili olan Türkçe’nin öğretiminde eğitim müşavirliğinin, bağlı eğitim ataşeliklerin ve Türkiye Cumhuriyeti tarafından görevlendirilen Türkçe öğretmenlerinin önemli yere sahip olduğu görülmüştür. Son olarak da Fransa’daki Türklerin dini gereksinimlerinin karşılanmasında Türkiye Cumhuriyeti Diyanet İşleri Başkanlığı’nın, Fransa’ya görevlendirilen din görevlilerinin ve Fransa’da bulunan DİTİP derneklerinin aktif rol üstlendiği sonucuna ulaşılmıştır.
Keywords: France; Turkish Diaspora; Identity; Turkish; Religion; Fransa; Türk Diasporası; Kimlik; Türkçe; Din